THE CUSTOMS AND EXCISE LAW ENFORCEMENT OF ILLEGAL CIGARETTE SMUGGLING IN BULI SARANI VILLAGE, EAST HALMAHERA REGENCY, INDONESIA - Muhammad Amin Hanafi; Puji Rahayu Subandi; Arief Budiono (RADJA PUBLIKA, 2026)
The circulation of illegal cigarettes is quite worrying because it is widely circulated and traded in a number of shops, supermarkets and stalls in most areas of Buli Sarani Village, East Halmahera Regency, potentially disrupting the cigarette company factory market and also excise revenues even with the large number of illegal cigarettes circulating without excise that are unstoppable, it also has an impact on public health because of unlimited use. This study aims to determine the duties and authorities of Customs and Excise in tackling the smuggling of illegal cigarettes in Buli Sarani Village, East Halmahera Regency and to determine the obstacles of Customs and Excise in preventing the smuggling of illegal cigarettes in Buli Sarani Village. The type of research used in this study is the empirical legal investigation method. In this study, the author uses a live case study approach as an approach to legal events where the trial is still ongoing. Due to the smuggling of illegal cigarettes, it causes many losses and negative impacts for the country and damages the nation's generation, because this criminal act of smuggling can hinder national development, the potential for state taxes disappears, and embarrasses the nation due to the collaboration between the Indonesian people and foreign parties in committing a form of crime. It is hoped that the results of this research can be used as reference material in the development of legal science, especially in the study of criminal law and criminal procedure law regarding law enforcement by customs in the criminal act of illegal cigarette smuggling.